Vegetação e Legislação Ambiental: Estudo de Regularização de Passivos Ambientais no Município de Ipiranga de Goiás – Goiás - Brasil - de Césaro, Silvana Gino Fernandes [UNESP]; Leal, Antonio Cezar [UNESP]; e Silva, Sandro Dutra (My University, 2024)
The primary forest that made up the Mato Grosso de Goiás region, and in which the municipality of Ipiranga de Goiás/GO is currently located, experimented from the 1940s onwards, through the “March to the West” policy”, a significant environmental suppression of this unique ecosystem. The forested areas of Matas de São Patrício, the northern portion of Mato Grosso de Goiás, suffered a strong impact from policies that favored the occupation of forests through incentives for land regularization, but above all from the creation of the National Agricultural Colony of Goiás (CANG). Currently, the remaining forest is within the territory of the Cerrado biome, a mapping created in 2004 that guides Brazilian environmental policies. Thus, this study reflects on the situation in this region, based on current legislation, but also points to historical elements. The lack of mandatory vegetation in Permanent Preservation Areas (APP) and Legal Reserves (RL) is a factor that negatively impacts the provision of Ecosystem Services (ES) and that is why Brazilian legislation requires them to be restored. Law 12,651/2012 created the Rural Environmental Registry (CAR), determining that all those responsible for rural properties with environmental liabilities must promote the restoration of legally protected and suppressed vegetation. The deadlines for these adjustments are in force throughout the country. Considering that in the municipality under study, native vegetation is limited to fragments due to land use that does not comply with the law, it is necessary to recompose these liabilities. This article presents a systematized proposal for connecting vegetation fragments, considering the ecological elements characteristic of forest remnants in the Cerrado, with the recomposition of vegetation in the municipality of Ipiranga de Goiás/GO, with the indication of the creation of Ecological Corridors in water APPs.
Keywords: ecological connection; Goiás; Mato Grosso de Goiás; rural environmental registry